The Long-Run Effects of California's Paid Family Leave Act on Women's Careers and Childbearing: New Evidence from a Regression Discontinuity Design and U.S. Tax Data - Martha Bailey; Tanya Byker; Elena Patel; Shanthi Ramnath (Center for Economic Studies and ifo Institute (CESifo), 2024)
We use administrative tax data to analyze the cumulative, long-run effects of California's 2004 Paid Family Leave Act (CPFL) on women's employment, earnings, and childbearing. A regression-discontinuity design exploits the sharp increase in the weeks of paid leave available under the law. We find no evidence that CPFL increased employment, boosted earnings, or encouraged childbearing, suggesting that CPFL had little effect on the gender pay gap or child penalty. For first-time mothers, we find that CPFL reduced employment and earnings roughly a decade after they gave birth.
Keywords: J08; J16; J71; 330; gender wage gap; maternity leave